2016
DOI: 10.15171/jcs.2016.033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Competence and Its Related Factors of Nurses in Neonatal Intensive Care Units

Abstract: Introduction: Clinical competence of nurses working in the neonatal intensive care units together with advancements in medical science and technology increased the survival rate of newborns that need specialized care. To ensure the quality of care and provide the safety of patients, evaluating the clinical competence of nurses seems necessary. This study aimed to evaluate the clinical competence of nurses in the neonatal intensive care units. Methods: In this cross-sectional study, 117 nurses working in the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 16 publications
(13 reference statements)
7
41
2
1
Order By: Relevance
“…From the head nurses' perspectives, the highest clinical competence is related to the management of clinical situations, while the lowest competencies are related to support and assistance and quality assurance [18]. In terms of managing clinical situations, the results presented here are consistent with those of Saeb (2016) [8,15].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…From the head nurses' perspectives, the highest clinical competence is related to the management of clinical situations, while the lowest competencies are related to support and assistance and quality assurance [18]. In terms of managing clinical situations, the results presented here are consistent with those of Saeb (2016) [8,15].…”
Section: Discussionsupporting
confidence: 84%
“…Hassankhani et al (2018) found that the overall competency of emergency nurses indicated a good level of perceived competence[18]. Valdez et al (2019) have suggested that higher competency levels in nurses in terms of management; decision making; and continuity of care, education, and cultural sensitivity, are related to shorter waiting times for patients[18].…”
mentioning
confidence: 99%
“…Some of the chest drains remain clogged and unnoticed by the nurses while others dislodge without prompt detection and intervention. There is prolonged hospitalization of patients with chest drains at KNH [16] [17].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Hassankhani et al (2017), Iranian emergency nurses, including both new and experienced, self-rated their competency level as good (Hassankhani et al, 2017). Mirlashari et al (2016) studied the clinical competence of Iranian nurses employed in the neonatal intensive care units and reported that 65.8% of these nurses had a moderate clinical competency (Mirlashari et al, 2016), as opposed to 53% in our study. The higher percentage of nurses with a moderate clinical competency level in Mirlashari et al's (2016) study can be due to recruiting both highly experienced and less experienced nurses (Mirlashari et al, 2016).…”
Section: Discussionmentioning
confidence: 62%